Da'wah bil Social Media: A Phenomenological Study of iGeneration TikTok Platform Users - Nasution, Nadya Amalia (Journal of Public Relations and Digital Communication (JPRDC), 2024)
This research examines the phenomenon of da'wah through social media (social media) carried out by iGeneration, especially UIN Raden Intan Lampung students, who are users of the TikTok platform. By using a phenomenological approach and integrating the Stimulus-Organism-Response (SOR) theory with the concept of social media "affordances,â€ this research aims to understand the experiences, strategies, and impacts of digital da'wah among Muslim students who use TikTok. Data collection methods include in-depth interviews, online participant observation, TikTok content analysis, and focus group discussions. The research results show that preaching content on TikTok acts as an effective stimulus, triggering cognitive and affective processes in the user (organism), which then produces a response in the form of increased religious awareness and changes in behavior. This research also reveals the critical role of TikTok affordances in shaping digital preaching practices and the ethical and theological challenges young preachers face. These findings provide in-depth insight into the transformation of da'wah practices in the digital era and the implications for Islamic education in higher education.Keywords: Digital da'wah, TikTok, iGeneration, SOR theory, media affordances, phenomenology